Técnicas de terapia manual empregadas para dor em pessoas com cefaleia: uma revisão de escopo - Melo, Eduardo Teixeira de (Brasil, 2022)
The aim of this review was to summarize the scientific evidence in order to verify the manual therapy techniques that are used for pain in people with headache. This study is a scoping review of the literature that was developed according to the JBI methodology and the PRISMA-ScR was followed. Studies carried out in people with headache of any type, regardless of sex, aged 18 years or older, who used manual therapy for headache treatment, in any clinical context and with any language, were considered. Searches were carried out in the information sources CINAHL, Embase, Google Scholar, LILACS, MEDLINE, PEDro, SciELO and Web of Science, from the beginning until 07/13/2022. Studies were selected by two independent reviewers using Rayyan. Data were extracted using a data extraction instrument developed by the reviewers themselves. Data were expressed in a tabular form with a narrative summary accompanying the illustrations. Ten studies were included, out of 1,402 possibly eligible records, with a combined population of 873 participants, ranging in age from 18 to 65 years. The most common headache types mapped were tension headache and migraine. Regarding manual therapy techniques, the most reported were PGM Therapy, Suboccipital Soft Tissue Inhibition Manual Therapy and Manual Therapy Based on Articulation Techniques. The most used pain measurement instrument was the visual analogue scale.